Alianças estratégicas e suas implicações para a configuração de capacidades tecnológicas: evidências da indústria farmacêutica multinacional - Ohba, Marisa (2005)
This dissertation examines the technological capabilities (techno-organizacional system, molecu1e and drug) , which were made available in strategic alliances by the multinacional pharmaceutical industry, as well as the ma in strategic alliances implications to the pharmaceutical industry in terms of the its technological capabilities configuration. These questions were examined based on the secondary empirical evidences regarding the strategic alliances in a sample of 25 multinational pharmaceutical industry companies of three groups: large pharmaceutical company (big pharma); large biopharmaceutical company (biopharma) and small intensive research companies. The related literature presentsa high number of studies about strategic alliances and technological capabilities in the multinacional pharmaceutical industry. But the theme about implications of such strategic alliances on the technological capabilities configuration changes still remains poor of more empirical fundamentation, according the entrepreneurial management perspective based on dynamic competences are more precisely, according the entrepreneurial strategy based on dynamic competences. This dissertation is based on an extensive and systematic survey of empirical evidences related to the strategic alliances, which were implemented by 25 pharmaceutical industry companies and published between 1993 and 2003. Such empirical evidences were surveyed with three data basis: Business & Industry; Galé and Dialog. In relation to the results, it was found that: In terms of participation with initial technological capabilities in strategic alliances: (i) the big pharmas entered with 11 % of 169 technological capabilities; (ii) the biophamas entered with 44% of 143 technological capabilities; (iii) the small intensive research companies entered with 72% of 95 technological capabilities. 2 In terms of implications of the strategic alliances on the configuration of techno10gical capabilities which entered into strategic alliances, it was found that: (i) the big pharmas increased the proportion of molecules (16% to 55%); (ii) the biopharmas increased the participation in molecules (22% to 32%) and technoorganizationa1 system to molecule research (49% to 55%); (iii) the small intensive research companies started a new activity (drug commercialization on pharmaceutical market) due to the drug proportion increase (3% to 29%). Additionally, they updated their techno-organizational system for molecule research. The evidences suggest that the cri teria for the partner and for the strategic alliance mechanism choices was dependent on the aims and needs of each pharmaceutical industry company group. Finally, while the integrated companies, big pharmas and biopharmas, mainly the first ones, have adapted the business model 'Fully Integrated Pharmaceutical Company' with the inclusion of strategic alliances to complement technological capabilities, the small intensive research companies take advantage on their technological capabilities through strategic alliances and they enter into the pharmaceutical market through the commercialization of the drugs acquired by strategic alliances. Therefore, the evidences suggest that the search for the knowledge basis complementation purposed to competion in a globalized market, has been involved, even informally, in a alteration on the innovative technological activities organization specially in terms of products (drugs).